2019
DOI: 10.1098/rsta.2018.0389
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics of delay systems: an overview

Abstract: Time delays play an important role in many fields such as engineering, physics or biology. Delays occur due to finite velocities of signal propagation or processing delays leading to memory effects and, in general, infinite-dimensional systems. Time delay systems can be described by delay differential equations and often include non-negligible nonlinear effects. This overview article introduces the theme issue 'Nonlinear dynamics of delay systems', which contains new fundamental results in this interdisciplina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…In contrast, studies in the field of nonlinear science have reported that transmission delays can stabilize systems [1][2][3]. For example, transmission delays between neurons are essential for inducing stable synchronization patterns in neural networks [4].…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, studies in the field of nonlinear science have reported that transmission delays can stabilize systems [1][2][3]. For example, transmission delays between neurons are essential for inducing stable synchronization patterns in neural networks [4].…”
Section: Introductionmentioning
confidence: 96%
“…In general, systems with delay, also called time delay systems, can be described by delay differential equations (DDEs). It is known that delays can have both stabilizing as well as de-stabilizing effects 15,16 . In DDEs the stability of a fixed point can switch from stable to unstable and back again multiple times under variation of the delay 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the focus was mainly on stability criteria for linear systems [9,30,60,65,84], be it Lyapunov-Krasovskii functionals [28,35,74], Lyapunov-Razumikhin functions [35], comparison principles [17,33,64], inputoutput approaches [8], or eigenvalue calculations [7,26,41,43]. By contrast, in technical applications, we encounter nonlinear systems [22,23,68,72,85]. Indeed, for a nonlinear system the Principle of Linearized Stability [21] allows to deduce stability or instability of equilibria, but the question arises: what is the practical relevance of knowledge about asymptotic stability if there is no knowledge about the domain of attraction?…”
Section: Introductionmentioning
confidence: 99%